Seafood Allergy in Asia: Geographical Specificity and Beyond - Wai, Christine Y. Y.; Leung, Nicki Y. H.; Leung, Agnes S. Y.; Wong, Gary W. K.; Leung, Ting F. (Frontiers in Allergy, 2021)
Asian countries have unique ways of food processing and dietary habits that may lead to profound differences in the prevalence, natural history, epidemiology and sensitization pattern of food allergic diseases when compared to western industrialized countries. Per capita consumption of seafood, including fish and shellfish, is way above the global average for many Asian countries because of their coastal geographical location and rich supply. The ready availability and high abundance in Asian countries have shaped a diverse way of processing and eating seafood, which are often in stark contrast with western countries. Such particularities can have a significant impact on the sensitization profile and allergenicity on seafood allergens. For example, fish and shellfish are eaten raw in some countries that may promote sensitization to heat-labile allergens not seen in other regions. Fermented fish sauce is commonly used as a condiment in some countries which may promote fish sensitization. Shrimp head and shrimp roe are regarded as delicacies in some countries but their allergen profiles are yet to be characterized. Freshwater fish and shellfish are a common food source in many Asian countries but the allergenicity of many freshwater species remain largely unknown. In this review, we discuss the possible factors that contribute to the differences in molecular profile and sensitization pattern observed in Asian populations and revisit the current findings of seafood allergy from the Asian perspective. Acknowledging the similarities and differences of seafood allergy patterns between Asian and western population can help us refine a better strategy for seafood allergy diagnosis and management with emphasis on geographical specificities.